Pengaruh Kualitas Produk, Promosi Dan Harga Terhadap Keputusan Pembelian Konsumen Buburbooth Di Rumah Sakit Awal Bros Sudirman Pekanbaru - Wahab, Wirdayani (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This study aims to determine the effect of product quality, promotion and price onÂ  consumer purchase decision to buburbooth at the Awal Bros Sudirman Hospital Pekanbaru. The sample of this research is 98 people. The technical data used is multiple linear regression using SPSS 17. Based on the results of the study, it was found that the product quality variable partially influenced the consumer purchase decision of Buburbooth on Awal Bros Sudirman Hospital Pekanbaru. The promosion variable partially influenced the consumer purchase decision of Buburbooth on Awal Bros Sudirman Hospital Pekanbaru. And the price partially has no effect the consumer purchase decision of Buburbooth on Awal Bros Sudirman Hospital Pekanbaru. There is a significant influence between product quality, promotion and price simultaneously or together on the consumer purchase decision of Buburbooth on Awal Bros Sudirman Hospital Pekanbaru